IMPLEMENTASI SISTEM RUJUKAN TERPADU DALAM PELAYANAN MATERNAL NEONATAL - Astri Ulina Saragih; Enrika T. Pasaribu; Septa Hayati Harahap (Politeknik Ganesha Medan, 2024)
Maternal mortality (MMR) and neonatal mortality (NIR) remain global health challenges, particularly in developing countries. One of the main causes is delays in receiving adequate care, often due to ineffective referral systems. The implementation of an integrated referral system in maternal and neonatal care aims to ensure that mothers and newborns requiring further care can access appropriate health facilities in a timely and efficient manner. This literature review examines the definition, principles, key components, benefits, and challenges of implementing an integrated referral system. The goal is to provide a comprehensive understanding of how this strategy can improve care coordination, reduce delays, and ultimately reduce maternal and neonatal morbidity and mortality.